La condamnation du mesmérisme revisitée - Bruno Belhoste (Revue d’Histoire des Sciences Humaines)
This article rereads the official inquiries that led to the condemnation of animal magnetism in 1784. It focuses on how the two investigating committees, the Royal Commission and the Commission of the Royal Society of Medicine, were constituted; how the investigations themselves were carried out, in the form of observations in the clinic of Dr Deslon, a disciple of Mesmer, and then in the form of experiments on isolated subjects (some of them for placebo effect); and finally how the reports were prepared and written. The aim is to show, on the basis of the numerous documents produced on this occasion, the complexity and contradictions of the investigations, the divisions between the investigators, and the fragility of the conclusions they reached. Using this famous case, the article thus illustrates the difficulty of arriving at certainties when it comes to evaluating medical treatments.